Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.0956-7976.2005.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Microgenesis and Ontogenesis of Perceptual Organization

Abstract: In two experiments, visual search and speeded classification were used to study perception of hierarchical patterns among participants aged 5 to 23 years. Perception of global configurations of few-element patterns and local elements of many-element patterns showed large age-related improvements. Only minor age-related changes were observed in perception of global configurations of many-element patterns and local elements of few-element patterns. These results are consistent with prior microgenetic analyses us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 40 publications
7
54
0
1
Order By: Relevance
“…In the absence of closure (i.e., the open stimuli), the discrimination between the concave and the convex stimuli cannot be based on shape properties but, rather, requires an explicit apprehending of the relative spatial placement of the two line segments for each stimulus. Thus, the age-related improvements for the open stimuli may be a result of improvements in spatial abilities (e.g., Kimchi et al, 2005;Stiles, 2001). Having demonstrated that young children are as good as adults in deriving the shape of a closed, connected figure, we now will turn to an examination of the ability of children and adults to utilize closure in fragmented figures as a function of the spatial proximity between the closure-inducing fragments and the presence or absence of collinearity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of closure (i.e., the open stimuli), the discrimination between the concave and the convex stimuli cannot be based on shape properties but, rather, requires an explicit apprehending of the relative spatial placement of the two line segments for each stimulus. Thus, the age-related improvements for the open stimuli may be a result of improvements in spatial abilities (e.g., Kimchi et al, 2005;Stiles, 2001). Having demonstrated that young children are as good as adults in deriving the shape of a closed, connected figure, we now will turn to an examination of the ability of children and adults to utilize closure in fragmented figures as a function of the spatial proximity between the closure-inducing fragments and the presence or absence of collinearity.…”
Section: Resultsmentioning
confidence: 99%
“…The growing body of research on perceptual organization suggests that not all groupings are equal in their time course, attentional demands, and developmental trajectory (e.g., Behrmann & Kimchi, 2003;Ben Av & Sagi, 1995;Kellman, 1996;Kimchi, 1998Kimchi, , 2000Kimchi, Hadad, Behrmann, & Palmer, 2005;Kimchi & Razpurker-Apfeld, 2004;Kovacs, Kozma, Feher, & Benedek, 1999;Kurylo, 1997;Quinn, Bhatt, Brush, Grimes, & Sharpnack, 2002;Spelke, 1982). This study focuses on the development of the ability to utilize closure and its combination with collinearity and proximity to organize fragmented image contours into shapes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Enns, Burack, Iarocci, Randolph, 2000;Kimchi, Hadad, Behrmann, Palmer, 2005;Porporino, Shore, Iarocci, Burack, 2004). As such, it is possible that the influence of perceptual grouping on performance is dependent on the task demands.…”
Section: Introductionmentioning
confidence: 99%
“…Now, one of the peculiarities of the Neanderthal/Denisovan skull is the so-called Neanderthal bun, a bump on the occipital part of the skull, corresponding to the primary visual cortex (V5, Brodmann area 17). While there is clearly more to conceptualization than perception, it is hard not to link the change in human conceptualization to the specificity of human perceptual preference for global processing of visual scenes (Navon, 1977;Kimschi et al, 2005) as opposed to non-human primate perceptual preference for local processing (Fagot and Deruelle, 1997;Fagot et al, , 2001. It is not impossible that the reorganization assumed by Boeckx and Benítez-Burraco also concerned the occipital area with capital consequences on visual preferences in modern humans, leading to improved conceptualization.…”
Section: The Language-ready Brainmentioning
confidence: 99%